A study on thermal stabilities of poly(2-methacrylamidopyridine)-poly(methyl methacrylate) blends - Coskun, M; Barim, G; Temüz, MM; Demirelli, K (Taylor & Francis Inc, 2005)
Blends of poly(methyl methacrylate) (PMMA) and poly(2-methacrylamidopyridine) (PMAP) obtained from free radical polymerization were prepared by casting films from CHCl3 solution, followed by drying for a few days. The blends were characterized by differential scanning calorimetry and Fourier transform infra-red spectroscopy. Single glass transitions indicate that the blend components are miscible. Thermogravimetric analysis shows that thermal stabilities of the blends are low compared to those of the homopolymer components. At lower temperatures, the cyclic imidation reaction effectively degrades the PMAP component in the blends and this reaction occurs at lower temperatures than does that of PMAP homopolymer because of hydrogen bonding between imine structures in PMAP and the ester carbonyl in PMMA. Thermal degradation of the blends has been followed up also as the (infrared) IR changes in them. Thermal degradation of the blend (PMMA:PMAP = 50:50 by wt) has been produced both in monomer in lower percentage and 2-aminopyridine in higher percentage compared with those of the homopolymers.
Keywords: poly(methyl methacrylate); poly(2-methacrylamidopyridine); cyclic imidation reaction